The Crisis of Parent-Child Relationships in Bernard Shaw's Play Mrs. Warren's Profession - Korbut Salman, Volha (Muş Alparslan Üniversitesi, 2018)
Bernard Shaw’s play Mrs. Warren’s Profession(1894) is applauded for its astute view of the corruption at the heart ofVictorian society. It centers on Mrs. Warren, who, forced by the economichardships of the nineteenth century London, becomes a prostitute and runsseveral successful brothels. Through her characterization, Shaw exposes socialcorruption and hypocrisy, and explores the personal consequences of such aprofession, as Mrs. Warren fails to gain respect and love of her daughterVivie, who discovers the truth about her mother’s occupation. The paper arguesthat it is the combination of social ills and negative personality traits thatdamage the conventional paradigm of parent-child relationships. To support theclaim, the paper investigates into the epitomes of Vivie’s reaction to hermother’s way of living that are going through various stages throughout theplay and culminating in Vivie’s final decision not to see Mrs. Warren again.

BernardShaw'ın Bayan Warren'ın Mesleği (1984) isimli oyunu, Viktoryen toplumunkalbindeki yozlaşmayı zekice betimlediği için takdir toplamıştır. Oyun, 19.yüzyıl Londra'sının ekonomik güçlükleriyle mücadele etmeye mecbur bırakılmış vebu yüzden hayat kadını olmuş olan ve başarılı birkaç genelev işleten BayanWarren’ın etrafında dönmektedir. Karakteri oluştururken Shaw, hem toplumsalyozlaşmayı ve ikiyüzlülüğü gözler önüne serer, hem de böyle bir mesleğiyapmanın kişisel sonuçlarını irdeler çünkü Bayan Warren, kendisinin mesleğihakkındaki gerçeği öğrenen kızı Vivie’nin saygı ve sevgisini kaybeder. Bumakale, bu durumun, geleneksel ebeveyn-çocuk ilişkilerine zarar veren toplumsalsorunların ve olumsuz kişilik özelliklerinin bir birleşimi olduğunu iddia eder.Bu iddiayı desteklemek için, bu makale, Vivie'nin, oyunun çeşitli aşamalarındagörülen, annesinin yaşadığı hayat tarzına karşı tepkilerinin örnekleriniinceleyecek ve Vivie'nin, Bayan Warren'ı tekrar görmek istemediğine dair sonkararı ile sonuçlanacaktır.
Bernard Shaw'ın Bayan Warren'ın Mesleği İsimli Oyunundaki Ebeveyn-Çocuk İlişkileri Krizi
anemon
Keywords: Bernard Shaw; Mrs. Warren’s Profession; Hypocrisy; Corruption; Parent-Child Relationships; Bernard Shaw; Bayan Warren’ın Mesleği; İkiyüzlülük; Ahlâk Bozukluğu; Ebeveyn-Çocuk İlişkileri